Organic-Photoacid-Catalyzed Glycosylation - Li, Juncheng; Zhao, Gaoyuan; Wang, Ting (Synlett, 2020)
Photoacids are molecules that become more acidic upon absorption of light. They are widely utilized in a variety of fields, such as organic synthesis, molecular switching agents, and photodynamic therapy. Currently, the activity of most photoacids is induced by UV light, which limits their applications by the synthetic community. In this Synpacts article, we highlight our recent development of visible-light-induced photoacids and their application in glycosylation reactions.1 Introduction2 Visible-Light-Induced Photoacids3 Synthesis of 2-Deoxyglycosides by Visible-Light-Induced Photoacid Catalysis4 Conclusion
Keywords: photoacids; glycosylation; 2-deoxyglycosides; visible-light; photocatalysis